Mapping Landslide Hazard and Risk Assessment Using GIS- Based Analytical Hierarchy Process and Weighted Linear Combination Methods in Gimbi Town, Western Ethiopia - Birhanu, Tadesa (ASTU, 2019)
In the present study, semi quantitative landslide hazard zonation and risk assessment for Gimbi Town (western Ethiopia) was carried out, and the environmental effects of landslides on further urban development were evaluated using geospatial techniques. For this purpose, four different group of data were used, namely: landslide inventories for validating final result, environmental factors like slope, aspect, lithology, soil type, elevation/topography, land use, Normalized Difference Vegetation Index and lineaments were used for landslide susceptibility map, triggering factors like rainfall was used for landslide hazard zonation, and element at risk like roads and settlement or built up area were used to map vulnerable at risk. Data of these factors were obtained from digital elevation model, satellite image (landsat8), secondary map, and field observation mapping. Nineteen event- based landslides inventories in the study area were also collected through field survey. Landslide hazard was produced from Landslide Susceptibility Map and rainfall map. Finally, landslide risk map was prepared from the integration of landslide hazard map and vulnerability map of elements at risk. In this study two Geographical Information System (GIS) based MultiCriteria Decision Analysis techniques like (1) Analytical Hierarchy process (AHP) was used to calculate the weights of associated criteria map layers and (2) weighted linear combination (WLC) was used to produce landslide hazard and risk map in a GIS environment. The results shows that 10.38%(4.83km2) of the study area falls in very high hazard, 29.22% (13.6 km2) in high hazard, 32.73%(15.24km2) in moderate hazard, 21.5% (10.01km2)in low hazard, and the remaining 6.17%(2.87 km2) in very low hazard zones, as well as 2.59%(1.2 km2) of the area falls in very high risk, 17.31% (11.77 km2) in high risk, 25.37%(11.77 km2) in moderate risk, 35.09%(16.28 km2) in low risk, and the remaining 19.64%(9.11 km2) in very low risk. Validation of landslide hazard zonation map with event based landslides showed that 89.5% of the landslides inventories points fall within moderate to very high hazard zones. Whereas validation of landslide risk zonation map with event based landslides showed that 68.4% of these landslides fall in moderate to very high risk zones. The veri???cation procedure proved that the produced landslide hazard and risk maps are important for land use management and planning in the study area. Thus, the landslide hazard and risk maps, that are produced in this study, will be useful to provide an important information about the locations of landslide prone areas and the levels of hazard and risk for land use planers and engineers so that they can implement suitable remedial measures for landslide disaster risk reduction and management.
Mapping Landslide Hazard And Risk Assessment Using Gis- Based Analytical Hierarchy Process And Weighted Linear Combination Methods In Gimbi Town, Western Ethiopia
Keywords: MCDA, GIS, Landslide, Hazard, Risk, Gimbi Town; Mcda, Gis, Landslide, Hazard, Risk, Gimbi Town